AB1005 Hypothyroid and hyperthyroid status was strongly associated with musculoskeletal ultrasonographic abnormalities with arthralgia. (15th June 2017) - Kim, BY; Kim, SS; Choi, JR; Kim, H-S
Abstract : Background: Thyroid dysfunction can cause musculoskeletal symptoms and sign. Ultrasonography is a useful tool for the evaluation of synovitis and is more accurate than clinical examination. Objectives: The purpose of the study was to determine whether musculoskeletal ultrasonographic (MSUS) abnormalities were observed according to the state of thyroid disease. Methods: Patients with thyroid disease were categorized as euthyroid, hypothyroid, or hyperthyroid status according to thyroid hormone levels and evaluated the association with MSUS abnormalities. In addition, the association of the presence of thyroid autoantibodies with MSUS abnormalities was also studied. In MSUS, an experienced rheumatologist examined the presence of synovial fluid, synovial hypertrophy, and grade of power doppler in the knee joint. Results: 109 consecutive patients who visited the endocrinology outpatient clinic and had thyroid disease with normal or abnormal thyroid function tests participated in the study. MSUS abnormalities were statistically significantly higher in hyperthyroid or hypothyroid status than in euthyroid status (p<0.001). However, there was no statistically significant difference between hypothyroid status and hyperthyroid status. The presence of MSUS abnormalities with abnormal thyroid function was corrected according to the presence of radiological Knee osteoarthritis. Both hypothyroid and hyperthyroid status was still associated with MSUS abnormalities regardless of knee osteoarthritis. Visual analogue scale for knee pain was higher in patients with MSUS abnormalities (p<0.001). But, there was no statistically difference of MGUS abnormalities with presence of thyroid autoantibodies. Conclusions: Both hypothyroid and hyperthyroid status was significantly associated with MSUS abnormalities with knee arthralgia. MSUS is a useful tool to detect clinically early joint abnormalities. We suggest that patients with diagnosed thyroid dysfunction and who remain uncontrolled, should assess the MSUS examination in patients with arthralgia. Moreover a thyroid function test for unexplained arthritis maybe warranted. References: Cakir M, Samanci N, Balci N, et al. Musculoskeletal manifestations in patients with thyroid disease. Clin Endocrinol 2003;59:162–7. Wakefield RJ, Green MJ, Marzo-Ortega H, et al. Should oligoarthritis be reclassified? Ultrasound reveals a high prevalence of subclinical disease. Ann Rheum Dis 2004;63:382–5. Magni-Manzoni S, Epis O, Ravelli A, et al. Comparison of clinical versus ultrasound-determined synovitis in juvenile idiopathic arthritis. Arthritis Rheum 2009;61:1497–504. Karim Z, Wakefield RJ, Quinn M, et al. Validation and reproducibility of ultrasonography in the detection of synovitis in the knee: a comparison with arthroscopy and clinical examination. Arthritis Rheum 2004:50:387–94. Disclosure of Interest: None declared